Quality of diet cookies added of passion fruit peel flour (Passiflora edulis) sensorially evaluated by diabetic - Batista Roque Santiago, Ariany Dágma; da Silva, Janilson Avelino; da Conceição, Maria Lúcia; de Souza Aquino, Jailane (O Mundo da Saúde, 2016)
The aim of this study was to develop to develop diet cookies added of passion fruit peel flourfor physicochemical, microbiological and sensory evaluation by patients with diabetes. Three types of cookies were formulated: control without passion fruit peel flour (B1) and two experimental cookies respectively added of 7 % (B2) and 10 % (B3) passion fruit peel flour. Initially, physicochemical and microbiological analyses were performed. The sensory test was performed by 87 patients with type II diabetes recruited from the Family Health Units of João Pessoa - PB. The flour of passion fruit peel showed 23.58 % fiber and 4.32 % minerals. Cookies added of passion fruit peel flour showed higher mineral (2.90 and 2.95 %) and fiber contents (3.20 and 3.65 %), and biscuit B3 showed higher protein content (15.5 %). All cookies showed desirable microbiological quality. The sensory scores ranged from “liked slightly” and “liked moderately” for all attributes evaluated, with no statistical difference between purchase intention and preference between cookies. The addition of passion fruit peel to cookies can be a viable alternative to diversify existing foods on the market aimed at people with diabetes.